2018
DOI: 10.18051/univmed.2018.v37.50-56
|View full text |Cite
|
Sign up to set email alerts
|

Flatfoot decreases school functioning among children < 11 years of age

Abstract: BACKGROUNDFlatfoot is a musculoskeletal abnormality commonly found in children that could result in a reduction of quality of life because of its related symptoms and functional abnormalities. This study aimed to determine the association between flatfoot and the quality of life among children 5-18 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…In a cross-sectional study that included children aged between 5 and 18 years, it was found that there were significant decreases in the quality of life in the school functioning domain among children younger than 11 years of age. 18 In addition, it has been reported previously that children with flexible flatfoot had significantly increased hindfoot eversion and forefoot supination during gait, which were significantly correlated with decreased quality of life. 19 Among patients who were prescribed orthoses, 65.9% were told that orthoses would correct the flat foot.…”
mentioning
confidence: 88%
“…In a cross-sectional study that included children aged between 5 and 18 years, it was found that there were significant decreases in the quality of life in the school functioning domain among children younger than 11 years of age. 18 In addition, it has been reported previously that children with flexible flatfoot had significantly increased hindfoot eversion and forefoot supination during gait, which were significantly correlated with decreased quality of life. 19 Among patients who were prescribed orthoses, 65.9% were told that orthoses would correct the flat foot.…”
mentioning
confidence: 88%
“…Penelitian mengenai kualitas hidup pada anak dengan flatfoot yang diadakan di United Kingdom oleh Kothari et al (2015) menjelaskan bahwa terdapat penurunan signifikan aspek kualitas hidup pada anak dengan flatfoot dibandingkan anak dengan normal feet. Penelitian Damayanti et al (2018) menyatakan bahwa terdapat penurunan kualitas hidup pada domain aktivitas fungsional sekolah pada anak usia < 11 tahun dengan flatfoot. Namun, tidak ada korelasi pada domain yang lain terhadap kualitas hidup anak.…”
Section: Tabel 3 Hasil Uji Beda Kelompok 2 (Kontrol) (N=15)unclassified